2021
DOI: 10.1186/s12967-021-02702-y
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of transthyretin and thyroxine-binding globulin in major depressive disorder: multiple reaction monitoring-based proteomic analysis

Abstract: Background Major depressive disorder (MDD), common mental disorder, lacks objective diagnostic and prognosis biomarkers. The objective of this study was to perform proteomic analysis to identify proteins with changed expression levels after antidepressant treatment and investigate differences in protein expression between MDD patients and healthy individuals. Methods A total of 111 proteins obtained from literature review were subjected to multiple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…One study found that serum TTR levels and RBP4/TTR ratio were essential markers of insulin resistance and gestational diabetes [ 78 ]. TTR also showed differentially expressed [ 79 ] in depressed patients, the transthyretin in depressed patients was more less.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that serum TTR levels and RBP4/TTR ratio were essential markers of insulin resistance and gestational diabetes [ 78 ]. TTR also showed differentially expressed [ 79 ] in depressed patients, the transthyretin in depressed patients was more less.…”
Section: Discussionmentioning
confidence: 99%
“…These non-enzymatic antioxidants account for more than 85% of the antioxidant capacity in plasma 34 . Prealbumin, known as transthyretin, which is a carrier protein for the transport of thyroxine and retinol and is also considered a non-enzymatic antioxidant 35 . Oxidative stress, which re ects an imbalance between reactive oxygen species and antioxidant mechanisms, has been suggested to be closely associated with MDD and BD 25 .…”
Section: Discussionmentioning
confidence: 99%